-(8y+5)-(-7y-8)=-1

Simple and best practice solution for -(8y+5)-(-7y-8)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8y+5)-(-7y-8)=-1 equation:


Simplifying
-1(8y + 5) + -1(-7y + -8) = -1

Reorder the terms:
-1(5 + 8y) + -1(-7y + -8) = -1
(5 * -1 + 8y * -1) + -1(-7y + -8) = -1
(-5 + -8y) + -1(-7y + -8) = -1

Reorder the terms:
-5 + -8y + -1(-8 + -7y) = -1
-5 + -8y + (-8 * -1 + -7y * -1) = -1
-5 + -8y + (8 + 7y) = -1

Reorder the terms:
-5 + 8 + -8y + 7y = -1

Combine like terms: -5 + 8 = 3
3 + -8y + 7y = -1

Combine like terms: -8y + 7y = -1y
3 + -1y = -1

Solving
3 + -1y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -1y = -1 + -3

Combine like terms: 3 + -3 = 0
0 + -1y = -1 + -3
-1y = -1 + -3

Combine like terms: -1 + -3 = -4
-1y = -4

Divide each side by '-1'.
y = 4

Simplifying
y = 4

See similar equations:

| 6(4x-9)=2(12x+8) | | 13-8x=73-29x | | 20x^2=45x | | -4x^2-20x-25=0 | | 0.18(12)+0.02x=0.06(24+x) | | 8+19n-3=7n+89-2n | | 2(3x-4)=5(8-2x) | | 7(2x-1)=3(15-4x) | | 6x^2+18=-21x | | -2v^2-5v-3=0 | | 1000=x+(x*.8)+(x*.3) | | 3.5q-1.4-5.9q=-3.4q-4.4 | | 1000=x+(x*.8)+(x*.5) | | -5y+4=-6y+5 | | 3x^2-14x=-18 | | 12x+6-3=11x-3 | | -10+3+6=-10 | | -4v^2-13v-3=0 | | -(8y+3)-(-7-4)=-1 | | 0.30(18)+0.05x=0.15(18+x) | | 8-4x+-6x=50 | | 4(2x-1)=2(3x+8) | | 4(3x+12)=2(2x+4) | | 1000=x+(x*.8) | | 3=2e^4x | | 9(x-36)=18 | | 2(x+4)=6(2x+3) | | 7(4x+6)+15= | | 4x-5=11-89 | | 6x+35=15x-55 | | 5a-3-4a+3=8 | | (4x^2+3x+5)-(6x^2-8)= |

Equations solver categories